Development trends in modern technology cooperation - Yu. M. Plotinskiy (Vestnik Moskovskogo Universiteta: Seriâ 18, Sociologiâ i Politologiâ, 2015)
The article discusses the features of the current stage of technology development cooperation in the information society. Shows how the development of new forms of cooperation could lead to negative consequences.